Contributions of Manufacturing Industries on Socio-economic Development Case of Tororo Cement Limited in Osukuru Town Councils in Tororo District - Ben Osilo (Uganda Christian University, 2025)
This study evaluated the contribution of Tororo Cement Limited to the socio-economic development of families in Osukuru town council. The objectives were to To find out the contribution of Tororo cement factory to the surrounding community, To establish the challenges faced by the families in Osukuru town council due to the presence of Tororo cement limited and to suggest strategies to address the challenges faced by families in Osukuru. This study used primarily utilize a mixed-methods approach employing both qualitative and quantitative approaches. A total of 250 were part of the study. The findings revealed that The factory has contributed to better roads and transport networks in the area, The company’s support for schools and hospitals has improved community welfare, Local businesses have benefited from the factory’s presence, Training programs by Tororo Cement have enhanced employable skills in the community, The challenges facing the community living near Tororo cement factory included Dust/emissions cause respiratory diseases (asthma, bronchitis), Industrial runoff pollutes groundwater, reducing clean water access , Noise from blasting/trucks disrupts sleep and quality of life. The Strategies to improve the lives of the community living near Tororo cement factory included Installations of electrostatic dust filters to reduce air pollution, Building water treatment plants to purify industrial runoff, Implement noise barriers and limit blasting to daytime hours land compensation framework The study concluded that Tororo Cement Factory has played a significant role in the socio-economic development of its surrounding community by creating employment opportunities, supporting local businesses and therefore recommended Increase investments in education, healthcare, and vocational training to empower local residents and enhance skills development.